International Marine Cargo Insurance: Building generic and thematic competences in commercial translation - Karina Socorro Trujillo (JoSTrans: The Journal of Specialised Translation)
This article highlights the importance of generic and thematic competences when translating commercial texts. It focuses specifically on the relevant theoretical framework for international marine cargo insurance and the genres produced within any claim procedure. The aim is to inform translators about the situational context and the documents involved when loss or damage to goods is incurred, and thus enable a greater command of the subject matter and tenor of discourse. Also highlighted is the importance of understanding the standardisation of words or expressions used in International Trade and Maritime Law with English as the lingua franca, together with the need to apply the correct translation strategies for the final purpose of the translation.